Instruction Quality or Working Condition? The Effects of Part-Time Faculty on Student Academic Outcomes in Community College Introductory Courses - Florence Xiaotao Ran; Jasmine Sanders (SAGE Publishing, 2020)
More than half of community college courses are taught by part-time faculty. Drawing on data from six community colleges, this study estimates the effects of part-time faculty versus full-time faculty on students' current and subsequent course outcomes in developmental and gateway courses, using course fixed effects and propensity score matching to minimize bias arising from student self-sorting across and within courses. We find that part-time faculty have negative effects on student subsequent enrollments. These negative effects are driven by results in math courses. We also find that course schedules could explain substantial proportions of the estimated negative effects, while faculty individual characteristics could not. Survey results on faculty professional experiences suggest that part-time faculty had less institutional knowledge regarding both academic and nonacademic services. We infer that inferior working conditions for part-time faculty, rather than inferior instructional practices, contribute to the negative effects we observed on students' subsequent course enrollment.